THE EFFECT OF Mg-Al Wt% FOR PHASE FORMATION OF SPINEL MgAl2O4 PRODUCED BY METAL DISSOLVED METHOD - Umamah, Chairatul; Pratapa, Suminar; Andi, Herman Jufri (Department of Physics, Maulana Malik Ibrahim State Islamic University of Malang, 2019)
Synthesis of magnesium aluminate spinel powder (MgAl2O4, abbreviated as MA) were prepared by the liquid mixing method. The synthesis of MA involved Mg powders with various weight compositions (4.8; 10; 20; 30; 40; and 60%) and Al powders (95.2; 90; 80; 70; 60 and 40%) as the raw materials, which were independently dissolved in 37% HCl to form MgCl2 and AlCl3 solutions. Both solutions were then mixed and stirred for 5 hours and dried to a temperature of about 100-105°C to produce powders with different weight compositions. Each powder resulted from drying was characterized using DTA-TGA, and then calcined at 650 °C; 750 °C and 850 °C for 1 hour. The calcined powder was characterized by XRD to qualitative and quantitative analyses using Rietica. It was found that MA samples contained only MgAl2O4 and MgO as the impurity phase. The relative weight fraction of MgAl2O4 increased up to 99% for 95.2 wt% Al. Using an extrapolative approach to determine the Mg-to-Al composition, nearly pure MA, as high as 99%, was achieved at 95.2% Al and 4.8% Mg.